Analisis Bahan Ajar Fisika Kelas X Berdasarkan Pilar Education for Sustainable Development (ESD) dan Science, Technology, Engineering, Art, and Mathematics (STEAM) - Wahyuni, Sri; Novita, Mega; Khoiri, Nur; Roshayanti, Fenny (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2023)
This study aims to analyze the teaching materials for grade X physics from two important perspectives, namely the ESD (Education for Sustainable Development) pillar and the Science, Technology, Engineering, Art, and Mathematics (STEAM) approach. The research method uses descriptive qualitative research. The population in this study was teaching materials for grade X physics used by teachers in Rembang Regency. The research instrument was a checklist of analysis instruments based on indicators of the Education for Sustainable Development pillars and STEAM components to obtain data. The results of the study found that the teaching materials used had implemented the ESD and STEAM pillars with an average percentage of occurrence of 12% for the socio-cultural pillar, 36% for the environmental pillar, 16% for the economic pillar, 87% in the Science component, 50% in the technology component, 57% in the engineering component, 77% in art, and 40% in the mathematics component. The results show that the implementation of the pillars of ESD and STEAM pillars in teaching books was still low.